Social stigma, social support and care-giving attitudes towards incarcerated persons by members of their families (2013)
The study examined the influence of social stigma and social support on care-giving attitudes towards incarcerated persons by members of their families. It was carried out in a correctional facility in Ibadan, using a cross-sectional design. Data was collected from 294 participants using standardized instruments. Results showed that social support had a significant positive relationship with care-giving attitudes at (r=.890; p<.05), while social stigma had a significant negative relationship with care-giving attitude at (r=-.798; p<05). Age, educational status, social stigma and social support had a significant joint influence on care-giving attitudes at F (4, 289),'=360.96; p<.05. However, only social stigma and social support had significant independent influence on the attitudes at (6= 302, t—8.341, p<.05) and 05-.665, t= 18 284, p<.05) respectively. These results suggest that for a caregiver of incarcerated persons, the stress of care giving is coupled with the constant threat of being stigmatized and discriminated against